KONSEP PENDIDIKAN TEKNOLOGI DAN KEJURUAN PADA ERA DIGITAL: SYSTEMATIC LITERATURE REVIEW 2020-2025 - Sayyoda, Fitra; Naufal, Naufal; Vaesar, Sahera Silvia; Abdullah, Rijal (Ensiklopedia Research and Community Service Review, 2025)
The digital era has changed the fundamentals of Technology and Vocational Education (PTK) around the world. This Systematic Literature Review (SLR) analyzes the transformation of PTK in the 2020-2025 period by synthesizing more than 80 academic sources. This study uses the PRISMA method to identify, select, and analyze relevant literature. The results of the study identified three main pillars of the transformation of PTK in the digital era: (1) TVET 4.0 conceptual framework that integrates cyber-physical systems, IoT, and AI technology; (2) The implementation of digital technologies such as VR, AR, and blended learning with varying effectiveness based on the learning context; (3) Development of digital competencies of teachers and students through frameworks such as DigCompEdu and UNESCO ICT CFT. The findings show that VR is effective for psychomotor skills (effect size g=0.85), but implementation faces challenges of infrastructure, teacher readiness, and digital divide. Link and match with Industry 4.0/5.0 demands a curriculum transformation that is responsive to the needs of 30-40% of employees who need reskilling. Case studies from Singapore, Germany, China, Indonesia, and Africa show a wide range of approaches and success rates. This study identified research gaps in methodology (qualitative dominance of 71%), limitations of longitudinal studies, and geographical disparities. Recommendations include strengthening empirical research, developing a specific digital competency framework for PTK, and policies that prioritize a people-first approach in digitalization.Keywords: Technology and Vocational Education, TVET, Digital Era, Industry 4.0, Digital Competence, Systematic Literature Review